Inclusive Economic Empowerment for Santika's Disabled Groups Based on Digital Storytelling for Local Product Branding - Sulasmi, Sulasmi; Suranto; Kusuma, Chusnu Syarifa Diah (Jurnal Ragam Pengabdian, 2026)
This Community Service program aims to enhance the capacity of disability groups in Kulon Progo by providing productive skills training, strengthening self-confidence, and delivering inclusive entrepreneurial mentoring. The program responds to several key challenges faced by partners, including limited access to disability-friendly vocational training, low levels of entrepreneurial literacy, inadequate marketing skills, and the absence of sustained mentoring after initial training activities. To address these issues, the program adopts a participatory and inclusive approach that actively involves participants in every stage of the process. The implementation methods include structured training sessions, hands-on practice tailored to participants’ needs and abilities, continuous mentoring, and systematic evaluation of participant satisfaction. This approach ensures that learning is practical, relevant, and empowering for all participants. The evaluation process is conducted using four primary indicators: the relevance and quality of training materials, the competence of resource persons, the adequacy of facilities and infrastructure, and the effectiveness of program implementation and follow-up activities. The findings reveal that participant satisfaction falls within the “very good” category across all indicators. Overall, this program has demonstrated a positive impact in increasing participants’ work motivation, improving basic entrepreneurial skills, fostering independence, and enhancing their readiness to engage in sustainable and more focused productive economic activities in the future.